Effect of annealing on superconducting properties of Bi1.6Pb0.4Sr2Ca2Cu2.2Zn0.8O10 thin films by pulsed laser deposition - Malike, Suzan (Iraqi Journal of Physics, 2011)
Superconducting thin films of Bi1.6Pb0.4Sr2Ca2Cu2.2Zn0.8O10 system were prepared by depositing the film onto silicon (111) substrate by pulsed laser deposition. Annealing treatment and superconducting properties were investigated by XRD and four probe resistivity measurement. The analysis reveals the evolution of the minor phase of the films 2212 phase to 2223 phase, when the film was annealed at 820 °C. Also the films have superconducting behavior with transition temperature ≥90K.